Self-Regulated and Online Collaborative Grammar Learning Via Google Multi-Platforms: Indonesian Case Study - Febriyanti, Rina Husnaini (JEdu: Journal of English Education, 2025)
Grammar acquisition is essential in learning English as the fundamental component in leveraging language skills. However, attaining the grammar competency optimally for Indonesian EFL learners encounters the challenges with various factors. Hence, a proper applicable approach is necessary to be adopted such as incorporating self-regulation strategy, online collaboration learning, and technology enhancement in grammar instruction. This study attempts to investigate the students perspectives in self-regulated and online collaborative grammar learning via Google multi-platforms. Employing a qualitative case study with questionnaires that distributed to 104 and 10 for the interviews of undergraduate sophomore students. The findings revealed that the participants positively perceived on self-regulated strategy and online collaborative grammar learning via Google multi-platforms. The implication of the current study can be as the consideration for educators, researcher, and technology developers relating utilizing online setting, collaboration activity, and technology aid in a grammar instruction.